Stratigraphy and Tectonics of the East Ketungau Basin, West Kalimantan during Palaeogene - Suyono, Suyono (Indonesian Journal on Geoscience, 2013)
DOI:Â 10.17014/ijog.v8i4.170East Ketungau Basin is one of frontier basins in Indonesia. Some of these basins, especially those in eastern Indonesia, have been identified to possess potential of oil and gas. The existing publications of geological fieldworks and extensive exploration in the East Ketungau Basin are limited. The detailed sedimentological and biostratigraphical studies of the sedimentary succession will be used to reconstruct the tectonic and palaeogeographical history of the basin. The sedimentary Mandai Group consists of three facies such as mudstone facies, clean sand facies and alternation between thinly coal seam, coaly shale, and claystone facies. However, each facies characterizes depositional environment of barrier- island and associated strand-plain systems.